House dust mite‐induced Akt‐ERK1/2‐C/EBP beta pathway triggers CCL20‐mediated inflammation and epithelial–mesenchymal transition for airway remodeling. Issue 9 (2nd August 2022) - Park, Shin‐Young; Kang, Min‐Jeong; Jin, Nuri; Lee, So Young; Lee, Yun Young; Jo, Sungsin; Eom, Jeong Yun; Han, Heejae; Chung, Sook In; Jang, Kiseok; Kim, Tae‐Hwan; Park, Jungwon; et al.
Abstract: House dust mite (HDM) allergens cause inflammatory responses and chronic allergic diseases such as bronchial asthma and atopic dermatitis. Here, we investigate the mechanism by which HDM induces C–C chemokine ligand 20 (CCL20) expression to promote chronic inflammation and airway remodeling in an HDM‐induced bronchial asthma mouse model. We showed that HDM increased CCL20 levels via the Akt‐ERK1/2‐C/EBPβ pathway. To investigate the role of CCL20 in chronic airway inflammation and remodeling, we made a mouse model of CCL20‐induced bronchial asthma. Treatment of anti‐CCL20Ab in this mouse model showed the reduced airway hyper‐responsiveness and inflammatory cell infiltration into peribronchial region by neutralizing CCL20. In addition, CCL20 induced the Nod‐like receptor family, pyrin domain containing 3 (NLRP3) inflammasome activation through NLRP3 deubiquitination and transcriptional upregulation in BEAS‐2B cells. As expected, anti‐CCL20Ab markedly suppressed NLRP3 activation induced by CCL20. Moreover, HDM‐induced CCL20 leads to epithelial–mesenchymal transition in the lung epithelium which appears to be an important regulator of airway remodeling in allergic asthma. We also found that anti‐CCL20Ab attenuates airway inflammation and remodeling in an HDM‐induced mouse model of bronchial asthma. Taken together, our results suggest that HDM‐induced CCL20 is required for chronic inflammation that contributes airway remodeling in a mouse model of asthma.